sistem rekomendasi pakan ikan lele menggunakan metode simple additive weighting - FATMAWATI, KAULA (Universitas Nusantara PGRI Kediri, 2024)
Abstract Catfish is a type of freshwater fish that is widely cultivated and is a source of income that has a high selling value among fish farmers in Indonesian society. Catfish is a fish that is easy to cultivate because of its adaptability so that catfish cultivation does not experience too many difficulties. However, it can have an impact on the harvest period and feed procurement if not controlled properly. Inappropriate feeding can inhibit the growth of catfish, resulting in less than optimal catfish cultivation. Due to this problem, to help catfish farmers avoid losses, a decision support system for feeding catfish using the Simple Additive Weighting (SAW) method is proposed, where this method is expected to be able to solve problems with several attributes by weighting so that they can provide alternative feed decisions. The method for recommending catfish feed is the SAW (Simple Additive Weighting) method which is used to determine the best alternative and a number of alternatives based on certain criteria. The system will carry out calculations using predetermined criteria including feed size, fish age and protein. The results of the system that has been created include: (1) the system was created based on existing problems, where the system is able to recommend catfish feed. (2) The Simple Additive Weighting Model method can be applied to recommend catfish feed based on predetermined criteria so that it can be used as a reference in decision making.